Frase-Frase Instruksional dalam Pembelajaran Bilingual di Sekolah Dasar - Rahma, Mutiara; Putri, Amanda; A, Anitasari; Wahyuningsih, Cahya Jesica; Hafidz, Arya Abdul; Widagdo, Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article aims to explain the definition of instructional phrases, the importance of using instructional phrases, and examples of instructional phrases in bilingual learning. This study employs a literature review method, relying on secondary data obtained from scholarly journals, articles, and textbooks relevant to instructional phrases in bilingual education. The findings indicate that instructional phrases are expressions used by teachers to give directions, commands, or guidance to students during the teaching and learning process. The use of instructional phrases in bilingual education is crucial for developing students’ communication skills, literacy, and comprehension in both languages, namely English and Indonesian. Examples of instructional phrases in bilingual learning include phrases used for giving orders, making requests, offering advice, providing instructions, issuing warnings, and functioning as speech acts.